Sex Specific Differences Recorded in the Behavior of an Amphipod: Implications for Behavioral Toxicology - Cherry, Taela-Rae; Kohler, Shanelle A.; Ford, Alex T. (Frontiers in Marine Science, 2020)
Behaviour is a useful endpoint in ecotoxicological research; it links the biochemical effects of contamination with physiology of individuals, which can be applied to higher levels of organisation with relevance to ecology. Animals exhibit species-specific and sex specific behaviours. Previous experiments within ecotoxicology using amphipods as models have either not separated by sex or have on the assumption that they may create more variability in the results. Therefore, the objectives of this study were to investigate the effect of time (which controlled light conditions), sex, and the interaction of time and sex on the swimming velocity in males and females of the marine amphipod Echinogammarus marinus. E. marinus exhibited a phototactic response to light, as is consistent with previous findings. It was determined that females swimming significantly faster than males and that this response was enhanced during periods when the lights were switched lights off. This suggests that a greater understanding of the baseline unconditioned behaviours of experimental organisms is needed to avoid impacts of unknown variables on results. The results of this study reveal significant sexual differences in the baseline behaviour of E. marinus which has implications for future research in ecotoxicology. It is recommended that in future research specimens be separated by sex prior to experimentation, in order to account for possible behavioural differences such as those observed in the present studies. This study also highlights the need for thorough observation of behaviour over shorter time intervals as larger intervals may miss short-term variations.